Assessment of risk factors associated with the level of physical activity in childhood and at the time of the survey in postmenopausal women with osteoporosis and vertebral body fractures - Nataliia Grygorieva; Оlena Rybina; Vladislav Povoroznyuk (Kharkiv State Academy of Physical Culture, 2018)
Today, discussions are continuing on the effect of regular exercise in childhood in preventing bone loss in postmenopausal women, as well as the positive effect of physical exercise (PE) in the prevention of osteoporotic fractures in older age groups. Purpose: to assess risk factors associated with the level of physical activity (PA) in childhood and at the time of the examination in postmenopausal women with osteoporotic and vertebral body fractures. Material & Methods: in a one-time study examined 115 postmenopausal women aged 50-89 years. For analysis, the patients were divided into two groups: I (control) group - persons without any osteoporotic fractures in history (n=84), II (main) group - patients with vertebral body fractures at the level of the thoracic and lumbar spine (n=31). With the help of a specially developed questionnaire, the authors evaluated the characteristics of the PA of patients at different age periods of life and at the time of the survey. Results: no significant differences were found in the frequency and types of sports in childhood between groups, depending on the presence of vertebral body fractures. The majority of patients with vertebral fractures (85,7%) began regular exercises of PA in childhood with the age of 10 years (41,7% in the control group, p=0,04), and in 57,1% of individuals the duration of these exercises was 1-4 years and did not differ from the control group. The frequency, type and duration of physical activity classes and the duration of physical therapy procedures, as well as the level of daily physical activity, did not significantly differ in women depending on the presence of vertebral body fractures, although the proportion of people who worked on a regular basis in sections was significantly higher among patients with vertebral fractures (41,9%) compared with individuals without fractures (10,7%, p=0,0002). In addition, the proportion of women in the control group who were physically active 6 or more hours per day was significantly higher (14,3%) compared with the corresponding indicator of the main group (3,2%, р=0,04). Conclusion: women with vertebral fractures were more often practiced regularly in sections and less physically active than those without fractures. The duration, regularity and age of starting sports in childhood can affect the risk of vertebral fractures in postmenopausal women, requires further study.